2017
DOI: 10.1002/jctb.5452
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous removal of selenite and phenol from wastewater in an upflow fungal pellet bioreactor

Abstract: BACKGROUND The simultaneous treatment of wastewater containing selenite and phenol in batch and continuous systems, inoculated with pellets of Phanerochaete chrysosporium, was evaluated in this study. RESULTS Synthetic oil refinery wastewater containing 15 mg L−1 selenite and 100–600 mg L−1 phenol was used in batch incubations for 5 days. Orange‐red colored pellets developed during selenite incubations in the presence of up to 400 mg L−1 of phenol, which confirms the formation of elemental selenium with remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In another study, 24 h was needed for P . chrysosporium to be effective in removing phenol from synthetic oil refinery wastewater 24 . From here, fungi was adjusted the environmental pH for the fungi to utilised the pollutant and lead to a reduction in the pollutant concentration.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, 24 h was needed for P . chrysosporium to be effective in removing phenol from synthetic oil refinery wastewater 24 . From here, fungi was adjusted the environmental pH for the fungi to utilised the pollutant and lead to a reduction in the pollutant concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Studies utilizing this fungus in the treatment of waste containing phenolic compounds have shown a rapid reduction in compound concentrations, reaching up to 90% within 12 hours of treatment [48]. Furthermore, in samples containing up to 100 mg/L of phenolic compounds, studies have observed an 80% reduction in just 5 days, utilizing an upflow fungal bioreactor featuring the activity of Phanerochaete chrysosporium [49].…”
Section: Characterization Of Publicationsmentioning
confidence: 99%